2013
DOI: 10.4047/jap.2013.5.3.248
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various intraoral repair systems on the shear bond strength of composite resin to zirconia

Abstract: PURPOSEThis study compared the effect of three intraoral repair systems on the bond strength between composite resin and zirconia core.MATERIALS AND METHODSThirty zirconia specimens were divided into three groups according to the repair method: Group I- CoJet™ Repair System (3M ESPE) [chairside silica coating with 30 µm SiO2 + silanization + adhesive]; Group II- Ceramic Repair System (Ivoclar Vivadent) [etching with 37% phosphoric acid + Zirconia primer + adhesive]; Group III- Signum Zirconia Bond (Heraus) [Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 30 publications
4
52
1
5
Order By: Relevance
“…MPa) [26]. However, the authors did not carry out thermal cycling and the specimen size was different from that of this study.…”
Section: Discussionmentioning
confidence: 75%
“…MPa) [26]. However, the authors did not carry out thermal cycling and the specimen size was different from that of this study.…”
Section: Discussionmentioning
confidence: 75%
“…It occurs because of their typical hydrophobicity, roughness, and surface area properties [7][8][9][10][11][12][13][14][15][16]. More recently, another field in which silanized silica materials have received special attention is their use as dental materials [17][18][19][20]. Tsai et al [21] made up a self-assembled film by deposition of silanized silica particles to obtain a surface with hydrophobic properties.…”
Section: Resultsmentioning
confidence: 99%
“…D' Acunzi et al [22] showed the use of silanized silica particles as a way to obtain superhydrophobic surfaces with the roughness adjusted by the drying process. Finally, Han et al [20] compared three resins for dental repair, and those obtained from silanized silica had significantly higher surface roughness. Figure 1(f) shows nanomechanical results obtained from force-distance curves of control and silanized silica surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…10 Elmas frezler ile aşındırma, ağız içinde tamir yapılacağı zaman kırık yüzeyinde sıkça kullanılan bir metottur. Aşındırma ile hem kırık yüzeyindeki kontaminasyon kaldırılmış olur 11 hem de diğer yöntemlere göre gözle görülebilir daha pürüzlü yüzeyler sağlayarak mekanik bağlantı sağlanmış olur. 12,13 Bu çalışmanın amacı, dört farklı yüzey işlemine tabi tutularak kompozit rezin ile tamir edilmiş zirkonya alt yapının yaşlandırma sonrası kompozit rezin ile olan makaslama bağlanma dayanımının değerlendirilmesidir.…”
Section: öRneklerin Hazırlanmasıunclassified